PENYULUHAN BUDIDAYA KEPITING SOKA SKALA RUMAH TANGGA DI DESA TANJUNG SELOKA KABUPATEN KOTABARU KALIMANTAN SELATAN - Rina Iskandar i22026; Frans Tony; M.Rezki Oktaviannoor (Fakultas Pertanian UVAYA Banjarmasin, 2024)
One of the important and potential economic commodities in Tanjung Seloka Village, Kotabaru Regency is crab cultivation which is very easy to implement in the Tanjung Seloka Community. One of the products is household-scale Soka Crab Cultivation, with an apartment system using plastic pond materials arranged vertically, equipped with water re-circulation. This business provides business opportunities for the people of Tanjung Seloka village, is a choice for the local government to drive the region's economy, and is a choice for the people of Tanjung Seloka. Domestic Scale Soka Crab Cultivation is delivered in the form of counseling/presentation of material and discussions. Community members who were present at the Tanjung Seloka village hall received direct material and explanations and had the opportunity to ask questions and discuss them, so that it was hoped that they could better understand and be able to apply them